Artificial urinary biomarkers for early diagnosis of acute renal allograft rejection - Cheng, Penghui (2023)
Acute renal allograft rejection (ARAR) after kidney transplantation associated with reduced graft survival and eventual graft failure is poorly diagnosed in hospitals. Here, we report the development of Artificial bioMarker Probes (AMPros) for sensitive urinalysis of ARAR in murine models. AMPros spontaneously go to the kidneys after systemic administration, specifically react with the prodromal immune biomarkers to activate their near-infrared fluorescence signals to report cell-mediated rejection, and efficiently undergo renal excretion into urine. Thus, AMPros enable convenient optical urinalysis that detects ARAR prior to histological manifestation of rejection, which is also earlier than current diagnostic methods measuring proinflammatory cytokines and peripheral blood lymphocyte mRNAs. Due to the high kidney specificity, AMPros-based urinalysis discriminates allograft rejection against other non-alloimmune specific diseases, which is unattainable by measurement of serological biomarkers. Such a noninvasive and sensitive urine test holds great promise in continuous monitoring of renal allograft conditions at low resource settings for timely clinical interventions.